Tribo-material based on a magnetic polymeric composite for enhancing the performance of triboelectric nanogenerator. (December 2020) - Sun, Ruixue; Gao, Lingxiao; Shou, Mengjie; Li, Bing; Chen, Xin; Wang, Fayang; Mu, Xiaojing; Xie, Lei; Liao, Changrong
Abstract: Magnetic polymeric composite has variable capacitance based on the adjustable arrangement of magnetic particles controlled by magnetic field. Considering the capacitive effect on the surface charge density of tribo-materials has important influence on the output performance of TENG, it is of great significance to study the magnetic polymeric composite as the tribo-material of TENG from a microscopic perspective. Here, an approach of using a magnetic polymeric composite film as the tribo-material is proposed to effectively enhance the output performance of TENG (M-TENG). After studying the inﬂuence of the cured magnetic flux density, filling particle concentration and particle size, a sustainable and enhanced output of 32.6 μA (short-circuit current) and 233.4 V (open-circuit voltage) were obtained, and a peak output power of 2.5 mW was gained from the M-TENG under a loading resistance of 3 MΩ, giving over 4.7-fold enhancement than the TENG which was based on the pure silicone rubber mixture film (0.53 mW). Finally, a real-time automatic target-scoring system was constructed to illustrate the practical value of M-TENG as a self-powered sensor. Graphical abstract: Magnetic polymeric composite has variable capacitance based on the adjustable arrangement of magnetic particles controlled by magnetic field. Considering the capacitive effect on the surface charge density of tribo-materials has important influence on the output performance of TENG, an approach of using a magnetic polymeric composite film as the tribo-material is proposed to effectively enhance the output performance of TENG. And a real-time automatic target-scoring system is constructed to illustrate the practical value of M-TENG as a self-powered sensor. Image 1 Highlights: The output of M-TENG enhanced by using a magnetic polymeric composite film as the tribo-material. The capacitance mechanism of the M-TENG was revealed clearly at the particle level. The effects of magnetic flux density, particle concentration and particle size were investigated. A real-time automatic target-scoring system with M-TENG as the self-powered sensor was developed.